Darwin day in America : how our politics and culture have been dehumanized in the name of science - West, John G. (Wilmington, Del. : ISI Books, 2007)
"Based on extensive research with primary sources and archival materials, John G. West's captivating Darwin Day in America tells the story of how American politics and culture have been corrupted by scientistic ideology. Marshaling fascinating anecdotes, and damning quotations." "West's narrative explores the far-reaching consequences for society when scientists and politicians deny the essential differences between human beings and the rest of nature. It also exposes the disastrous results that ensue when experts claiming to speak for science turn out to be wrong. West concludes with a plea for the restoration of democratic accountability in an age of experts."--Jacket.
Nothing buttery from atomism to the Enlightenment -- Darwin's revolution -- Criminal science -- Crime as mental illness -- Turning punishment into treatment -- Law of the jungle -- Breeding our way out of poverty -- The science of business -- Building the world of tomorrow -- Darwin day in America -- Banned in Burlington -- Junk science in the bedroom -- Sex miseducation -- Redefining life -- Redefining death.
Includes bibliographical references and index.
committed to retain
Keywords: Darwin, Charles, -- 1809-1882 -- Influence; Science -- Social aspects -- United States; Social Darwinism; Religion and politics -- United States; Social values -- United States; Influence (Literary, artistic, etc.); Politics and government; Religion and politics; Science -- Social aspects